CONSIDERATIONS ON COVID 19 IMPACT ON AGRICULTURE AND FOOD SECURITY AND FORWARD-LOOKING STATEMENTS - Mirela PARASCHIVU; Otilia COTUNA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The COVID 19 pandemic is one of the greatest threats of the 21st century that disturbed whole human's life and all sectors of the global economy. Due to highly infectious and spreading capacity of SARS-CoV-2 the governments took unprecedented measures worldwide with a great impact on the most vulnerable groups (people affected by chronically hunger, malnourished children and small farmers) and sectors. Agriculture is the most important economic sector that cares the responsibility for food security and human development. The present paper identifies and synthetize relevant literature to provide an integrated overview of the current state-of-knowledge on the economic impact of COVID 19 pandemic on agriculture and food security, including also forward-looking statements on future measures to mitigate the effects on crop production, food demand, agricultural products supply, inputs supply, agricultural products market, farmers' income and rural poverty. The study emphasizes that due to the mobility restrictions, decline in international trade, reduced purchasing power, disturbance in food production and food processing, food insecurity may arise affecting especially the small farmers from the regions already affected by poverty, climate change and conflicts. Therefore, the governments and international organizations should enforce the measures to control the pandemic, with minimum economic losses, without disturbing the food supply chain and re-enforcing the food security of their citizens.